Knowing and being known: Psychedelic–assisted psychotherapy and the sense of authenticity - Fischman, Lawrence G. (Frontiers in Psychiatry, 2022)
Participants in MDMA- and psychedelic-assisted psychotherapy often emerge from these treatments with new beliefs about themselves and the world. Studies have linked changed beliefs with mystical experiences reported by some participants during drug sessions. While there has been some debate about the epistemic value of drug-induced mystical experiences, and about the need for consent to treatments that may alter metaphysical beliefs, less attention has been given to the sense of authenticity that attends these experiences. In this paper, I consider the intersubjective context in which these changed beliefs arise. I suggest that the sense of authenticity people experience with MDMA- and psychedelic-assisted psychotherapy derives from a simultaneous feeling of knowing and being known. The medications used in these treatments reduce the defensive barriers which ordinarily prevent powerful feelings from being intersubjectively shared, allowing the subject to experience knowing and being known with the therapist and/or internalized or imagined others. In explaining this thesis, I discuss Ratcliffe's “existential feeling;” ipseity in incipient psychosis and psychedelic states; Winnicott's notions of the True Self, omnipotence, creativity, and transitional phenomena; implicit relational knowing and moments of meeting; infant-mother dyad research; predictive processing and the relaxed beliefs model of psychedelic action; the role of the “partner in thought” in knowing and feeling known. I propose that a “transitional space” model of MDMA- and psychedelic-assisted psychotherapy is well-suited for working through “not-me” or dissociated experience